On behalf of others the psychology of care in a global world - Scuzzarello, Sarah; Kinnvall, Catarina; Monroe, Kristen R., 1946- (New York ; Oxford : Oxford University Press, 2009)
'On Behalf of Others' offers both a theoretical and empirical discussion of the psychology of ethics and care in a global world. The book takes an interdisciplinary approach to understanding how political, economic, social and psychological forces interact and are mutually reinforced in a global context.
Includes bibliographical references and index.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Globalization -- Moral and ethical aspects